2011
DOI: 10.9721/kjfst.2011.43.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gingerols in Various Fractions and the Antioxidant Effects of Supercritical Fluid Extracts from Ginger

Abstract: Ginger (Zingiber officinale Rosc.) is a well known edible plant that is traditionally used to treat various illnesses related to inflammation and oxidative stress. Steam distillated ginger oil or water extract are mainly used for related products; however, it is unclear whether these fractions contain most of the bioactive compounds or the highest efficacy. This investigated the antioxidant effects of extracts prepared by supercritical fluid extraction (SFE). 6-Gingerol was the most abundant component in hexan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…Several recent studies have shown that Z. latifolia is effective in reducing insulin resistance, suppressing hyperlipidemia, reducing blood glucose levels, exerting antiobesity effects, and preventing skin aging [21][22][23][24]. Lee et al [25] demonstrated that a methanol extract of Z. latifolia exhibits antiallergic effects through the inhibition of compound 48/80-induced degranulation and antigen-induced ß-hexosaminidase release in RBL-2H3 mast cells. Another study reported that one new flavonolignan, one flavone, and three flavonolignans were isolated as the active constituents from the ethyl acetate fraction of the aerial parts of Z. latifolia, and that tricin and its derivatives were the main components of Z. latifolia [26].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown that Z. latifolia is effective in reducing insulin resistance, suppressing hyperlipidemia, reducing blood glucose levels, exerting antiobesity effects, and preventing skin aging [21][22][23][24]. Lee et al [25] demonstrated that a methanol extract of Z. latifolia exhibits antiallergic effects through the inhibition of compound 48/80-induced degranulation and antigen-induced ß-hexosaminidase release in RBL-2H3 mast cells. Another study reported that one new flavonolignan, one flavone, and three flavonolignans were isolated as the active constituents from the ethyl acetate fraction of the aerial parts of Z. latifolia, and that tricin and its derivatives were the main components of Z. latifolia [26].…”
Section: Introductionmentioning
confidence: 99%
“…생강은 특유의 맛과 향기를 지니고 있어 기호성이 좋은 향신료의 하나 로써 날 생강, 건 생강, 정유(absolute, oleoresin) 등이 생강 제품을 위 한 소재로 유통되고 있다 (Lee et al, 2011).…”
unclassified
“…환류 냉각 추출법은 식물의 가용성 물질을 안정적으로 추출할 수 있으나 많은 용매가 필요하며 추출 과정에서 많은 시간이 소요되는 단점이 있다 (22). 또한, 초임계 유체 추출법은 기능성 물질을 추출하는 속도가 빠르며 용매의 소비량이 적고, 저온에서도 조작할 수 있어 열에 민감한 천연물질의 추출에 유용한 장점이 있지만 많은 비용이 드는 단점을 내포하고 있다 (23,24). 각 추출방법들이 가진 문제 점들을 보완하기 위한 적절한 대안으로 마이크로웨이브추 출(microwave-assisted extraction, MAE)이 주로 사용되고 있다 (25) Table 3).…”
unclassified